Self, knowledge, and freedom : essays for Kalidas Bhattacharyya - Bhattacharya, Kalidas; Mohanty, Jitendranath, 1928-; Banerjee, Sankari Prasad, 1930- (World Press, 1978)
Festschrift honoring Kalidas Bhattacharyya, b. 1911, Indian scholar of philosophy.